2012
DOI: 10.1007/s00406-012-0318-7
|View full text |Cite
|
Sign up to set email alerts
|

Disturbed dreaming and sleep quality: altered sleep architecture in subjects with frequent nightmares

Abstract: Nightmares are intense, emotionally negative mental experiences that usually occur during late-night sleep and result in abrupt awakenings. Questionnaire-based studies have shown that nightmares are related to impaired sleep quality; however, the polysomnographic profile of nightmare subjects has been only scarcely investigated. We investigated the sleep architecture of 17 individuals with frequent nightmares and 23 control subjects based on polysomnographic recordings of a second night spent in the laboratory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
79
3
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(89 citation statements)
references
References 47 publications
4
79
3
3
Order By: Relevance
“…There are a number of small studies that have reported variable PSG characteristics in nightmare sufferers. [43][44][45][46][47][48][49] REM-specific abnormalities to include absence of early REM periods, increased REM sleep latency, and increased REM periods, as well as NREM changes to include reduced slow wave sleep, have been reported. 44,46 Other studies note more global changes to include increased sleep latency, sleep fragmentation, nocturnal awakenings, and periodic limb movements.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are a number of small studies that have reported variable PSG characteristics in nightmare sufferers. [43][44][45][46][47][48][49] REM-specific abnormalities to include absence of early REM periods, increased REM sleep latency, and increased REM periods, as well as NREM changes to include reduced slow wave sleep, have been reported. 44,46 Other studies note more global changes to include increased sleep latency, sleep fragmentation, nocturnal awakenings, and periodic limb movements.…”
Section: Discussionmentioning
confidence: 99%
“…[43][44][45][46][47][48][49] REM-specific abnormalities to include absence of early REM periods, increased REM sleep latency, and increased REM periods, as well as NREM changes to include reduced slow wave sleep, have been reported. 44,46 Other studies note more global changes to include increased sleep latency, sleep fragmentation, nocturnal awakenings, and periodic limb movements. 41,43,45,46 The most consistent PSG finding is an increase in overnight awakenings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although questionnaire-based studies have shown that nightmares are related to impaired sleep quality (Lancee, Spoormaker, & van den Bout, 2010;Li, Zhang, Li, & Wing, 2010;Schredl, 2003), and NM participants exhibit significantly worse values on sleep-and health-related indexes (Krakow, 2006), the sleep architecture of NM individuals has scarcely been investigated. After the first inconclusive results (Fisher, Bryne, Edwards, & Kahn, 1970;Germain, & Nielsen, 2003), a recent study (Simor, Horváth, Gombos, Takács, & Bódizs, 2012) found that NM participants are characterized by altered sleep architecture showing impaired sleep continuity and emotion-related increases in REM propensity reflected by reduced sleep efficiency, increased wakefulness, a reduced amount of slow-wave sleep (SWS), and an increased number of nocturnal awakenings, especially from Stage-2 (S2) sleep.…”
mentioning
confidence: 99%
“…Simor et al [6] used polysomnographic recordings to investigate the sleep architecture of 17 individuals with frequent nightmares compared to 23 controls and found reduced sleep efficiency, increased wakefulness, reduced amount of slow wave sleep plus increased nocturnal awakenings, especially from Stage 2 sleep, in nightmare probands. They furthermore exhibited longer durations of REM sleep due to heightened negative affect.…”
mentioning
confidence: 99%